2020
DOI: 10.1155/2020/8284931
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms Predict Overall Survival and Cancer-Specific Survival in Patients with Fibrosarcoma: A SEER-Based Study

Abstract: Purpose. Due to the rarity, it is difficult to predict the survival of patients with fibrosarcoma. This study aimed to apply a nomogram to predict survival outcomes in patients with fibrosarcoma. Methods. A total of 2235 patients with diagnoses of fibrosarcoma were registered in the Surveillance, Epidemiology, and End Results database, of whom 663 patients were eventually enrolled. Univariate and multivariate Cox analyses were used to identify independent prognostic factors. Nomograms were constructed to predi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Many of the descriptive statistics for our patient cohort provide support for the previously reported characteristics of patients diagnosed with FS. We found that FS is slightly more common in males than females, which is consistent with other sources that report a very slight male predominance [ 3 , 12 , 13 ], although an equal sex incidence has also been reported [ 1 , 13 ]. If there is a true difference in sex incidence, it is likely minimal.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many of the descriptive statistics for our patient cohort provide support for the previously reported characteristics of patients diagnosed with FS. We found that FS is slightly more common in males than females, which is consistent with other sources that report a very slight male predominance [ 3 , 12 , 13 ], although an equal sex incidence has also been reported [ 1 , 13 ]. If there is a true difference in sex incidence, it is likely minimal.…”
Section: Discussionsupporting
confidence: 92%
“…However, due to the rarity of cases, factors affecting the overall survival of FS have not been comprehensively studied. Male sex, older age, advanced stage, higher grade, increased tumor size, and not receiving surgical treatment have been reported to be associated with decreased overall survival [ 13 ]. The goal of our study is to further assess prognostic variables for FS.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely available prediction tools is nomogram, a visualizing survival prediction model. [7][8][9][10] Recent studies have developed a nomogram to predict the overall survival (OS) for LCNEC. 11 However, as far as we are aware, nomograms for predicting the CSS of patients with LCNEC have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…e prognostic factors associated with OS and cancerspecific survival in fibrosarcoma have been reported in previous studies [26]. However, the study included patients of all ages, which makes it questionable whether the results of the study are fully applicable to older patients with fibrosarcoma.…”
Section: Discussionmentioning
confidence: 94%
“…Even in this particular group of elderly patients, there is a tendency for the prognosis to deteriorate with age. First of all, it is probably since older patients are usually more likely to suffer from chronic diseases or postoperative complications, making them more likely to die [ 26 ]. Secondly, as older patients are generally in worse health, surgeons may hesitate to treat older patients as intensively and aggressively as younger patients, leaving older patients undertreated [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%